Determinants of Primary Healthcare Utilization in Remote Archipelagic Communities: The Roles of Patient Attitudes, Provider Support, and Social Networks - Korjesin, Jeane Westy; Prasetyo, Joko; Wardani, Ratna (KHD Production, 2026)
Community Health Centers serve as critical primary healthcare providers, yet optimizing patient utilization in remote regions remains challenging. This study analyzes the influence of patient attitudes, health worker support, and social support on the interest in utilizing health services at the Larat Community Health Center. An observational, quantitative, cross-sectional design was employed to evaluate these psychosocial determinants among 389 respondents selected through purposive sampling from a total population of 14,354. Multiple linear regression analysis assessed the simultaneous and partial effects of the independent variables on interest in service utilization. Descriptive statistics revealed that 48.8% of respondents had adequate attitudes, 56.3% perceived sufficient health worker support, and 55.0% reported adequate social support, while 51.9% demonstrated a medium level of interest in utilization. The regression model demonstrated a highly significant simultaneous influence (p-value = 0.000), with these three variables collectively explaining 67.7% of the variance in patient interest. Healthcare utilization interest emerges as a complex behavioral outcome driven by the dynamic interplay among individual mindsets, clinical staff support, and community networks, rather than by isolated individual choices. Policymakers must implement integrated, holistic interventions that address all three psychosocial pillars to sustainably enhance primary care engagement, improve health literacy, and reverse declining visit rates in marginalized archipelagic communities.